2015
DOI: 10.1080/20477724.2015.1103501
|View full text |Cite
|
Sign up to set email alerts
|

Presence ofWuchereria bancroftimicrofilaremia despite 7 years of annual ivermectin monotherapy mass drug administration for onchocerciasis control: a study in north-west Ethiopia

Abstract: Background: There is considerable interest in determining whether mass drug administration (MDA) with ivermectin for onchocerciasis control will eliminate coendemic lymphatic filariasis (LF). The objective of this study was to determine the prevalence of LF microfilaremia in onchocerciasis endemic districts that had received 7 years of MDA with ivermectin. Method: Three villages with a 2010 LF circulating antigenaemia prevalence (determined in a mapping exercise using immunochromatography tests) ranging from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…It was found that inspite of 6 rounds of MDA, Mf prevalence was 3.3%. The authors had suggested mass distribution of DEC medicated salt as an adjunct to hasten elimination of infection in these islands. 7 South East AsiaIndonesiaDewi et al, 2015109Three communities (one non endemic,one passed TAS,one failed TAS)1,543 children6–7Ab prevalenceThis study provided the epidemiological support for the use of Ab levels to determine “critical cut-off thresholds” in Brugia spp. areas.…”
Section: Monitoringmentioning
confidence: 69%
See 1 more Smart Citation
“…It was found that inspite of 6 rounds of MDA, Mf prevalence was 3.3%. The authors had suggested mass distribution of DEC medicated salt as an adjunct to hasten elimination of infection in these islands. 7 South East AsiaIndonesiaDewi et al, 2015109Three communities (one non endemic,one passed TAS,one failed TAS)1,543 children6–7Ab prevalenceThis study provided the epidemiological support for the use of Ab levels to determine “critical cut-off thresholds” in Brugia spp. areas.…”
Section: Monitoringmentioning
confidence: 69%
“…One study assessed the possibility of integrating antibody testing for LF and oncho, which has highlighted the complexities that may arise in making a decision on stopping MDA particularly in LF-oncho co-endemic areas of Africa 111. Another study109 observed that 7 years of monotherapy with ivermectin has not reduced Mf prevalence in a oncho-LF co-endemic area and therefore to achieve significant reduction, the authors suggested that albendazole be added to the program particularly in LF endemic areas. In another oncho-LF co-endemic area118 the study showed that while Mf and Ag rates were reduced by 83% and 67%, the mosquito infection and infectivity rates were reduced by 86% and 76% compared to the baseline.…”
Section: Monitoringmentioning
confidence: 99%
“…The baseline mapping results showed antigenemia prevalence ranging from 23 to 56% in these villages. After seven years of ivermectin treatment the mean microfilaremia prevalence in the three villages was still 4.7% [10]. These studies suggest that annual ivermectin may reduce prevalence of infection but may not be sufficient to interrupt transmission.…”
Section: Introductionmentioning
confidence: 99%
“…For parasites, Trichinosis, Toxoplasmosis and Onchocerciacis are common transmissible parasitic diseases from wild animals, including deer, and a number of studies on their characterization and prevention have been performed [ 4 , 11 , 16 ]. Regarding Sarcocystis (Protozoa: Apicomplexa), many species have already been identified in other animals, such as S. cruzi , S. hirsuta and S. bovihominis in cattle; S. miescheriana, S. porcifelis and S. suihominis in pigs and S. tenella and S. mihoensis in sheep [ 1 , 10 , 15 , 24 , 33 , 35 , 36 ].…”
mentioning
confidence: 99%